Fabrication of Polypropylene/Poly (Trimethylene Terephthalate) Blend Fibers with Highly Improved Resiliency and Preserved Mechanical Properties. Issue 1 (2nd January 2019) - Habibolah Zargar, Mohammad Reza; Shoushtari, Ahmad Mousavi
Abstract: The main aim of this study was to deal with one of the major drawbacks of polypropylene (PP) fibers, i.e. low resiliency, by incorporating poly (trimethylene terephthalate) (PTT) nano-fibrils as a dispersed material into the PP polymer matrix. Thanks to the special helical shape of the PTT polymer backbone, the incorporated nano-fibrils of the PTT polymer strengthened the resiliency of the blend fibers. The presence of 10 and 15 wt% of PTT in the blend fibers led to an approximately 20% increase in the resilience behavior, compared to pure PP fibers, with the mechanical properties of the PP matrix preserved. The development of the fibrillar structures during the different steps of the melt spinning process was confirmed by scanning electron microscopy (SEM), and the lowest mean diameter of the nano-fibrils was 64 nm for the hot drawn blend fiber samples consisting of 10 wt% of PTT. In summary, we suggest the optimized blend fiber samples produced in this research will be a promising candidate for a wide range of engineering applications.